THE EFFICIENCY OF ASEAN SHARIA BANKS FOR THE 2013-2013 PERIOD: TWO-STAGE STOCHASTIC FRONTIER ANALYSIS - Ivana Rosediana Dewi; Bayu Arie Fianto (Universitas Airlangga, 2020)
This study aims to determine the influences of internal and external variables of Islamic banks towards technical efficiency (TE)of Islamic banks in ASEAN 2013-2018. The data represented the sample from each country. The study was analyzed using two-step processes. The first stage is looking for technical efficiency (TE) with the Stochastic Frontier Analysis (SFA) as an intermediation approach. The second stage is conducting panel data regression analysis to determine the influence of internal and external variables of Islamic banks towards TE score. The result of the study indicates that the average TE value of Islamic banks in ASEAN at the periods of the study has very good efficiency of 0.92 (92.8 percent). Respectively, Islamic banks in Indonesia have TE score higher than Malaysia. Meanwhile, Islamic banks in Brunei Darussalam have the highest TE score, followed by Islamic banks in Thailand and the Philippines. The variable of total assets (lnTA), Degree of Capitalization (EQTA), and Bank's Financing Intensity (FINTA) have a positive and significant effect on the value of TE and the variable of economic growth (GDP) and inflation rate (CPI) have no effect on TE of sharia banks.Keywords: Technical Efficiency, Islamic Bank, ASEAN, Stochastic Frontier AnalysisREFFERENCE Abdul-majid, A. M., Saal, D. S., Battisti, G., Journal, S., August, N., & Saal, M. A. D. S. (2016). Efficiency in Islamic and conventional banking : an international comparison efficiency in Islamic and conventional banking : an international comparison, 34(1), 25–43.Aigner, D., Lovell, C. A. K., & Schmidt, P. (1977). Formulation and estimation of stochastic frontier production function models. Journal of Econometrics, 6(1), 21–37. Al-Gasaymeh, A. (2016). Bank efficiency determinant: Evidence from the gulf cooperation council countries. Research in International Business and Finance, 38, 214–223. Alqahtani, F., Mayes, D. G., & Brown, K. (2017). Islamic bank efficiency compared to conventional banks during the global crisis in the GCC region. Journal of International Financial Markets, Institutions and Money, 51, 58–74. Athanasoglou, P., Delis, M., & Staikouras, C. (2006). Determinants of bank profitability in the South Eastern European Region. MPRA Paper No. 10274, Posted 20 Sep 2008 04:31 UTC, (10274).Barry, T. A., Dacanay, S. J. O., Lepetia, L., & Tarazi, A. (2012). Ownership structure and bank efficiency in the asia pacific region. Beck, T., Demirguc-Kunt, A., & Maksimovic, V. (2004). Bank competition and access to finance: International evidence. Journal of Money, Credit, and Banking, 36(3b), 627–648. Berger, A. N., & DeYoung, R. (2001). The effects of geographic expansion on bank efficiency. Journal of Financial Services Research, 19(2–3), 163–184. Berger, A. N., & Humphrey, D. B. (1997). ScienceDirect.com - European Journal of Operational Research - Efficiency of financial institutions: International survey and directions for future research. European Joumal of Operational Research, 98, 175–212. Berger, A. N., & Mester, L. J. (1997). Inside the black box : What explains differences in the efficiencies of financial institutions ? 1, 21, 895–947.Budiantoro, R. (2019). Mengukur efisiensi Bank Pembiayaan Rakyat Syariah (BPRS) dalam pembiayaan UMKM menggunakan Stochastic Frontier Analysis di Provinsi Jawa Timur, Triwulan I/2012-Triwulan IV/2017. Tesis tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis. Universitas Airlangga.Christopher Findlay; Friska Parulian; Jenny Corbett; (2010). Linkages between real and financial aspects of economic integration in East Asia, 28(September), 350.Coelli, G. E. B. J. (1995). Battese-Coelli-1995. Empirical economics, 20, 325–332.Coelli, T. J., Prasada Rao, D. S., O’Donnell, C. J., & Battese, G. E. (2005). An introduction to efficiency and productivity analysis. An Introduction to Efficiency and Productivity Analysis. Drake, L., & Hall, M. J. B. (2003). Efficiency in Japanese banking: An empirical analysis. Journal of Banking and Finance, 27(5), 891–917. Eyceyurt Batir, T., Volkman, D. A., & Gungor, B. (2017). Determinants of bank efficiency in Turkey: Participation banks versus conventional banks. Borsa Istanbul Review, 17(2), 86-96. Farrell, M. J. (1957). The measurement of productive efficiency. Journal of the Royal Statistical Society. Series A (General), 120(3), 253–290. Fries, S., & Taci, A. (2005). Cost efficiency of banks in transition: Evidence from 289 banks in 15 post-communist countries. Journal of Banking and Finance, 29(1 SPEC. ISS.), 55–81. Hauner, D. (2005). Explaining efficiency differences among large German and Austrian banks. Applied Economics, 37(9), 969–980. Iveta, Ř. (2015). Banking efficiency determinants in the czech banking sector, 23(October 2014), 191–196. Johnes, J., Izzeldin, M., Pappas, V. (2014). A comparison of performance of Islamic and conventional banks 2004–2009. Elsevier B.V, (October), 15. Kamaruddin, B. H., Safa, M. S., & Mohd, R. (2008). Assessing production efficiency of Islamic banks and conventional bank Islamic windows in Malaysia, (61160).Kamarudin, F., Sufian, F., Loong, F. W., & Anwar, N. A. M. (2017). Assessing the domestic and foreign Islamic banks efficiency: Insights from selected Southeast Asian countries. Future Business Journal, 3(1), 33–46. Karray, S. C. (2013). Bank size and efficiency in developing countries: intermediation approach versus value added approach and impact of non-traditional activities Jamel eddine Chichti. Asian Economic and Financial Review, 3(5), 593–613. Kumar, S., & Gulati, R. (2014). Measurement of bank efficiency: Analytical methods. Lin, K. L., Doan, A. T., & Doong, S. C. (2016). Changes in ownership structure and bank efficiency in Asian developing countries: The role of financial freedom. International Review of Economics and Finance, 43, 19–34. Mačerinskiene, I., & Ivaškevičiute, L. (2008). The evaluation model of a commercial bank loan portfolio. Journal of Business Economics and Management, 9(4), 269–277.Meesters, A. J. (2009). Efficiency of financial institutions Meesters, A.J. University of Groningen, 9–12.Meeusen, W., & van Den Broeck, J. (1977). Efficiency estimation from cobb-douglas production functions with composed error. International Economic Review, 18(2), 435. Mokhamad Anwar. (2014). Bank efficiency and lending propensity: Evidence from commercial banks in Indonesia. School of Management University of Leicester, 1–251.Mokhtar, H. S. A., Abdullah, N., & Alhabshi, S. M. (2006). Efficiency of Islamic banking in Malaysia: a Stochastic Frontier Approach. Humanomics, 27(2), 37–70. Mongid, A. (2016). Business efficiency of the commercial banks in asean. Investment Management and Financial Innovations, 13(1), 67–76. Nahm, D., & Vu, H. (2013). Profit efficiency and productivity of Vietnamese banks: A new index approach. Journal of Applied Finance and Banking, 3(1), 1–31. Nguyen, T. L. A. (2018). Diversification and bank efficiency in six ASEAN countries. Global Finance Journal, 37, 57-78. OJK. (2017). Booklet perbankan Indonesia 2017. Purnamandari, N., & Badera, I. (2015). Kemampuan prediksi rasio keuangan dan ukuran bank pada risiko gagal bank. E-Jurnal Akuntansi, 12(2), 172–187.Rismawati, R. (2016). Menghadapi qualified Asean bank, Indonesia: Berekspansi Atau Bertahan Di Dalam Negeri? Veritas et Justitia, 2(1), 154-176. Rosman, R., Wahab, N. A., & Zainol, Z. (2014). Efficiency of Islamic banks during the financial crisis: An analysis of Middle Eastern and Asian countries. Pacific Basin Finance Journal. Rozzani, N., & Rahman, R. A. (2013). Determinants of bank efficiency: Conventional versus Islamic. International Journal of Business and Management, 8(14), 98-109. Solihin, S., Achsani, N. A., & Saptono, I. T. (2016). the Islamic banking and the economic integration in Asean. Buletin Ekonomi Moneter Dan Perbankan, 19(1), 81–106. Subandi, & Ghozali, I. (2013). Determinan efisiensi dan dampaknya terhadap kinerja profitabilitas industri perbankan di indonesia. Jurnal Keuangan Dan Perbankan, 17(1), 123–135.Sufian, F., & Akbar Noor Mohamad Noor, M. (2009). The determinants of Islamic banks’ efficiency changes: Empirical evidence from the MENA and Asian banking sectors. International Journal of Islamic and Middle Eastern Finance and Management, 2(June),120-138. Sufian, F., & Kamarudin, F. (2015). Determinants of revenue efficiency of Islamic banks. International Journal of Islamic and Middle Eastern Finance and Management, 8(1), 36–63. Sufian, F., Mohamad, A. . N., & Muhamed-Zulkhibri, A. M. (2009). The tfficiency of Islamic banks: Empirical Evidence from the MENA and Asian countries Islamic banking sectors. J for International Business and Entrepreneurship Development, 5(2), 154-166.Tahir, I. M., Mongid, A., & Haron, S. (2012). The determinants of bank cost inefficiency in ASEAN banking. Jurnal Pengurusan, 36(January 2012), 69–76.Todaro, M. P., & Smith, S. C. (2003). Economic development: The Addison-Wesley series in economics.Wensveen, D. Van. (2003). The theory of financial intermediation: an essay on what it does (not) explain by Bert Scholtens Vienna 2003.Yudistra, D. (2003). Efficiency in Islamic banking: An empirical analysis of 18 banks. Islamic Financial Architecture - Risk Management and Financial Stability, 44(0), 479–496.